La presencia de la catalasa y la calidad panificable de la harina de trigo - Albizzati, Carlos M. (1938)
The author exposes a series of analytical conclusions on wheat flour and applies the biometrical calculation in the values obtained, proving that a certain correlation exists between the contents in ashes and the activity of the cátalase the same thing does not occur between the activity of the catalase and the volume of the bread an analytical datum this last which is used to prove the bread-making quality of the flour. He considers therefore that the determination of the said enzime does not signify an element for judging the value of the quality's flour.